ETHICAL NORMS IN USING AI TECHNOLOGIES FOR TRANSLATING CHILDREN’S LITERATURE - ZOKIROVA, Naimakhon Shokirjon qizi (The Lingua Spectrum, 2025)
This article examines the ethical dimensions of using artificial intelligence in the translation of children’s literature, focusing on issues such as cultural preservation, age-appropriate language, and the expressive nuances of the original text. The study highlights the risks associated with AI-generated translations, including the loss of emotional depth, stylistic integrity, and culturally specific elements essential for a child’s cognitive and moral development. At the same time, the article acknowledges the potential benefits of AI, such as increased efficiency and support in creating draft translations and glossaries. Ultimately, it emphasizes that AI can be ethically integrated into the translation process only when combined with human oversight, professional judgment, and a commitment to maintaining the educational and cultural value of children’s literature.